2018
DOI: 10.1155/2018/6265182
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment of Sporadic Burkitt’s Lymphoma Causing Ileocaecal Invagination

Abstract: Introduction Primary NHL (non-Hodgkin lymphoma) of the colon represents only 0.2% to 1.2% of all colonic malignancies. Burkitt's lymphoma (BL) is usually a disease reported in children and young people, most of them associated with EBV or HIV infection. We describe a rare case of intestinal obstruction due to sporadic Burkitt's lymphoma causing ileocaecal invagination explaining our experience Methods. A 31-year-old man presented with diffuse colic pain and weight loss. Clinical examination revealed an abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although, no microperforation was reported, unlike our case. 3 Small bowell perforation due to BL literature is scarce, with the first reported case registered in 2021 by Takayama et al 2 As pointed by the authors, there are several articles reporting gastrointestinal perforation occurred during chemotherapy in BL, but the first case reporting intestinal perforation due to BL was by Takayama's team. A midline laparotomy approach was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, no microperforation was reported, unlike our case. 3 Small bowell perforation due to BL literature is scarce, with the first reported case registered in 2021 by Takayama et al 2 As pointed by the authors, there are several articles reporting gastrointestinal perforation occurred during chemotherapy in BL, but the first case reporting intestinal perforation due to BL was by Takayama's team. A midline laparotomy approach was used.…”
Section: Discussionmentioning
confidence: 99%
“…2 BL stands for 9% of the cases of primary small intestine lymphoma and clinical presentations includes intestinal obstruction or intussusception, small bowel perforation or as an incidental finding. [1][2][3][4][5][6][7] We presented a case of intestinal obstruction by the form of ileum to cecum intussusception secondary to a Burkitt's lymphoma in a middle-aged man with signs of microperforation. platelet count.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with BL has significantly changed with the advent of short, intensive chemotherapy. Several agents, including bleomycin, cyclophosphamide, vincristine, doxorubicin, and highdose methotrexate, provide excellent response rates [11] achieving a complete response rate of 85%, with a five-year disease-free survival rate of 60% [5,9,10,12].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of factors might play a role in intestinal invaginations; The most important cause of intestinal invaginations in adults is malignancies [1,3,4,[6][7][8][9][10][11][12]. It has also been reported that the etiologic reason is malignancy, especially in colonic invaginations [13].…”
Section: Mini-review Articlementioning
confidence: 99%
“…In a similar study by Kaemmerer et al, it was reported that adenovirus infections cause CD3 positive lymphocyte infiltration, which causes enlargement of Peyer's patches and mesenteric lymph nodes due to inflammatory neuropathy in the mesenteric plexus, which is the cause of ileocecal invaginations [5]. Some cases are etiologically less common in adults, including intraluminal lipoma in the ileum [15][16][17], endometriosis in the appendix and ileum [18], inflammatory fibroid polyp (Vanek tumor) [19,20], due to colonoscopy [21], Meckel's diverticulum [22], intestinal tuberculosis [4], transmural diffuse large B cell lymphoma infiltration [23], idiopathic [24], submucosal colonic lipoma [2,25], Chron's disease [26], leiomyoma in the ileum [27], Burkitt lymphoma [28], cases of induced intestinal invagination have been reported.…”
Section: Mini-review Articlementioning
confidence: 99%